Equilibrium, kinetic and thermodynamic studies of ethanol adsorption by polydivinylbenzene-silica - Divinagracia, Maricor F.; De Luna, Mark Daniel G.; Chung, Tsair-Wang (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Adsorption of Ethanol onto polydivinylbenzene-silica (PDVB/R-SiO2) has been studied using batch adsorption techniques.The adsorbent has been studied as a function of contact time, temperature and initial ethanol concentration.The amount of ethanol adsorbed per gram of PDVB/R-SiO2 increased with increasing contact time and initial concentration while a reverse trend was observed when the temperature was increased.Adsorption isotherms have been modeled by Langmuir and Freundlich isotherms.A comparison of kinetic models was evaluated for the pseudo-first-order, pseudo-second-order and intra-particle diffusion kinetics models.The isothermal data could be well described by the Freundlich equation,while the dynamical data fit well with the pseudo-second-order kinetic model.Thermodynamic parameters such as activation energy(Ea) and change in the free energy (AG0),the enthalpy (AH0),and the entropy (AS0) were also evaluated.Instrumental analysis BET,XRD,FT-IR and SEM were also done to further confirm the effectiveness of PDVB-SiO2) as ethanol adsorbent.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman
Keywords: Ethanol -- Adsorption; Silica gel; Ethanol as fuel